2020
DOI: 10.1111/age.12895
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study to identify genetic loci associated with gastrointestinal nematode resistance in Katahdin sheep

Abstract: Summary Resistance to gastrointestinal nematodes has previously been shown to be a moderately heritable trait in some breeds of sheep, but the mechanisms of resistance are not well understood. Selection for resistance currently relies upon faecal egg counts (FEC), blood packed cell volumes and FAMACHA visual indicator scores of anaemia. Identifying genomic markers associated with disease resistance would potentially improve the selection process and provide a more reliable means of classifying and understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
14
0
3
Order By: Relevance
“…A plethora of constantly updated reports [ 17 , 40 , 41 ] of SNPs associated with TBP and GIN, as well as the heritability estimates between low to medium values in the present study (see Table 2 ) confirm the importance of genomics for livestock improvement. Even though this study has discovered findings of such potential, they should be interpreted with caution due to the large standard errors of the estimates.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A plethora of constantly updated reports [ 17 , 40 , 41 ] of SNPs associated with TBP and GIN, as well as the heritability estimates between low to medium values in the present study (see Table 2 ) confirm the importance of genomics for livestock improvement. Even though this study has discovered findings of such potential, they should be interpreted with caution due to the large standard errors of the estimates.…”
Section: Discussionsupporting
confidence: 82%
“…Although most species of the bovine Onchocerca (ONC) parasites have been reported non- or low-pathogenic [ 16 ], their importance mainly being a naturally occurring model for the closely-related human parasite. Traits associated with disease resistance have already been found to be heritable, with identified regions mapped by genome-wide association studies (GWAS), even if at times with low estimates [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These genetic selection strategies can be facilitated by using traits with relatively high heritability (e.g., faecal egg counts [FEC], haematocrit, body condition). For example, immunity against H. contortus expressed as FEC and packed cell volume values is a heritable trait in sheep [ 230 ], and there are differences among different breeds in Haemonchus infection. However, some studies in Merino sheep breeds have concluded that selection for low H. contortus FEC may also lead to lower animal production [ 228 , 231 ].…”
Section: Challenge Iv: Future Controlmentioning
confidence: 99%
“…Publications from this effort have already reported potential SNP for identification of allelic variants associated with resistance to GIN (Becker et al . 2020 ).…”
Section: Future Applications Of Genomicsmentioning
confidence: 99%